Preclinical evaluation of the antitumor activity of bortezomib in combination with vitamin C or with epigallocatechin gallate, a component of green tea - Bannerman, Bret (Springer-Verlag, 2011)
PURPOSE: To investigate whether clinically relevant levels of epigallocatechin gallate (EGCG, a component of green tea) or vitamin C (ascorbic acid) could antagonize bortezomib antitumor activity in CWR22 human prostate xenograft tumors. METHODS: The pharmacokinetics (PK) of EGCG and ascorbic acid were determined in immunocompromised mice and compared with concentrations measured in human PK studies of dietary supplements. Antitumor activity of bortezomib in combination with EGCG or ascorbic acid was determined using several dosing regimens to evaluate different target plasma concentrations of EGCG and ascorbic acid. RESULTS: Bortezomib dosed twice-weekly at 0.8 mg/kg IV demonstrated tumor growth inhibition (TGI) of 53.9–58.9%. However, when combined with EGCG such that the plasma concentrations of EGCG were >200 μM at the time of bortezomib dosing, all antitumor activity was abrogated (TGI = −17.7%). A lower concentration of EGCG (11–16 μM), which is severalfold higher than measured clinically in humans taking EGCG supplements (0.6–3 μM), was not antagonistic to bortezomib (TGI 63.5%). Pharmacodynamic studies of proteasome inhibition reflected these findings. Ascorbic acid (40 and 500 mg/kg PO daily) was evaluated under a similar study design and did not antagonize bortezomib antitumor activity (TGI 57.2 and 72.2%). CONCLUSIONS: No antagonism of bortezomib is seen in preclinical in vivo experiments, where EGCG or ascorbic acid plasma concentrations are commensurate with dietary or supplemental intake. The data suggest that patients receiving bortezomib treatment do not need to avoid normal dietary consumption of green tea, vitamin C-containing foods, or EGCG or vitamin C dietary supplements. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s00280-011-1591-2) contains supplementary material, which is available to authorized users.